Predictors of psychological stress occurring after the first wave of the COVID-19 pandemic in Poland: A cross-sectional study - Długosz, Piotr (Frontiers in Psychiatry, 2023)
The article presents the results of research aimed to identify the predictors of psychological distress among Poles seven months after the occurrence of the first case of COVID-19. In order to gather the research material, the CAWI on-line survey method was applied and carried out within the framework of the Ariadna Research Panel on the sample of 1079 Poles aged 15 and over. The results of the conducted research indicate that Polish society experienced psychological distress during the first wave of the pandemic. According to the Kessler Psychological Distress Scale (K10), no mental disorders were observed among 36% of Poles, mild mental disorders were observed among 23% of respondents, average levels of disorders were observed among 18% of respondents, whereas high levels of disorders were observed among 23% of respondents. A hierarchical linear regression analysis was used to identify the risk factors of psychological distress. In the first stage, socio-demographic variables explained 13% of the distress variance. In the second stage, the variables measuring social nuisances of the pandemic were introduced, which increased the percentage of the explained stress variance to 24%. In the third stage, the introduced psychological variables increased the percentage of the explained variance to 65%. The main factor which increased stress levels was neuroticism. The conducted analyses have shown that the lack of social, economic and psychological capital significantly increases the susceptibility to distress when a threat to life and health lasts for a prolonged period of time.